Os determinantes do Índice de Gestão Calórica das crianças das famílias do Programa Cartão Mais Infância – Ceará - Meneses, David Aguiar de (2021)
The current work aims at analyzing the main features related to Caloric Intake index from children covered by the Programa Cartão Mais Infância Ceará. This issue calls into question the need for figuring out whether that income transfer program is being sufficient enough to provide their food security. As a way of fulfilling this target, it was required to use cross-section data centered around an econometric model, i.e, Feasible Generalized Least Squares, appealing to Ruel and Menon (2002). The database used comprises families living in the cities of Canindé, Baturité and Maracanaú.